Processos de Markov via o adjunto formal dos operadores de Feller - Speroto, Adalto (2012)
The main aim of this work is the study of spectral properties of a class of the second order operators, the formal adjoint of the generalized Feller diferential operators. In particular, to deduce that these operators are generators of a strongly continuous contraction semi-group and therefore, to obtain a corresponding class of Markov processes. As a secondary objective, we will establish some results for stochastic processes. We will establish the connection of Markov processes, operators and infinitesimal generators of semi-groups.